PARTISIPASI MASYARAKAT DALAM MUSYAWARAH PERENCANAAN PEMBANGUNAN KOTA BINJAI TAHUN 2013 - , ARVINTONA ISKANDAR D; , Prof. DR. Wahyudi Kumorotomo, MPP. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The implementation of regional autonomy is inseparable from the planning that comes from the top and the bottom comes from planning. The legislation requires national development planning system development planning requires the participation of the community in the process of drafting the planning. Development planning discussion (Musrenbang) is an intergovernmental forum of stakeholders in order to devise a sustainable development plan. Musrenbang executed terraced by involving community participation so as to produce a work plan in favour of the community. Therefore, this research attempts to examine about community participation in development planning discussion Binjai 2013 in order to devise a work plan for regional development town of Binjai. The research was conducted using a mixed methods i.e. with qualitative and quantitative approach. Qualitative and quantitative approaches used to see the degree of public participation in the musrenbang Binjai and proposed community in drawing up the work plan regional development Binjai. The degree of public participation in the musrenbang views by using the theory of participation that has been said by Sherry Arnstein. Engineering data collection done by interviews, questionnaires and documentation study The results showed that the participation of the community in the town of Binjai musrenbang were still on a degree of tokenism (bode) in accordance with the theory of Arnstein. Public participation is still limited to convey the proposal development authority, however the decision was in the hands of the Government. The community does not have the authority in determining the direction and development policy to be implemented. A representative system in the musrenbang also results in weak bargaining positions of society in the formulation of planning. The study also illustrates the position of the proposed society are still weak where the number of proposed Community fixed on one sector of development is not able to diakomodir all because of keterbatasaan the budgets of every government agency Binjai Community participation in the musrenbang needs to be improved with the delegation of authority to the community and the society as a parallel position as subjects of development with the principles of community empowerment. Binjai City Government needs to do is widely disseminated related priorities and budgetary capability so that the community can deliver the proposals in accordance with their needs.